Dialog Antaragama: Membangun Pemahaman Bersama dalam Perspektif Islam dan Katolik - Kristianus Adrianto Virando; Silfanus Jemadin; Elfridus Darmin; Florianus Syukur; Yanuarius Juliano Sukardi; Adrianus Ednal Julio; Hironimus Raldi Bot (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Religious pluralism in Indonesia constitutes a unique national identity, yet it is vulnerable to horizontal conflicts and acts of intolerance. This study aims to analyze the importance of interfaith dialogue in fostering mutual understanding from Catholic and Islamic perspectives within Indonesia’s pluralistic society. The methodology employed is qualitative research using a literature review approach, involving the collection and analysis of various relevant sources such as books, journals, and academic articles. The results of the study indicate that both Islam and Catholicism possess strong theological foundations in support of interfaith dialogue, emphasizing openness, respect for differences, and a commitment to peace and coexistence. Interfaith dialogue has proven to be an effective means of addressing divisions or conflicts, combating intolerance, and fostering harmonious relationships within a multireligious society. Furthermore, it was found that barriers to dialogue are still influenced by factors such as fanaticism, a lack of understanding, and socio-political conditions. This study concludes that interfaith dialogue is a strategic approach to strengthening tolerance and national unity. Therefore, it is recommended that interfaith dialogue be continuously developed through education, interfaith cooperation, and the active role of religious leaders in fostering inclusive and sustainable communication.